PERAN HUMAN RESOURCES DEPARTEMENT (HRD) DALAM MENGEMBANGKAN FUNGSI CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN ETIKA ISLAMI DALAM ORGANISASI - Cucu Komala (Ekonomi Islam, 2021)
Human resource development (HRD) is increasingly expected to play a facilitative role in sustainable corporate social responsibility and ethics in organizations. However, there is also significant skepticism regarding HRD's ability to make contributions to these fields. The company's value will grow in a sustainable manner if the company does not only pay attention to profitability but also guarantees the company's social and environmental dimensions. The role of HRD is criticized for moving away from its mission to advocate human values "‹"‹in organizations. At the same time ensuring that the company or organization is able to run well in accordance with business ethics in order to form a company that has credibility, responsibility, transparency, independence, and fairness. This article describes the framework of activities used by HRD in its role on social and ethical aspects of Islam as a sustainable work culture This research method is a systematic literature review method by synthesizing research results that are related to the topic or study discussed. implementation of Islamic values "‹"‹in the world of work and is significantly successful because through ethical work a person can express himself and contribute to the community. The role of HRD is an inseparable part of building CSR and Islamic ethics that have guiding values right for the organization. Keywords: HRD, CSR, and Islamic Ethics